2008
DOI: 10.5539/elt.v1n1p121
|View full text |Cite
|
Sign up to set email alerts
|

Reading from the Wordless: A Case Study on the Use of Wordless Picture Books

Abstract: For centuries people have conveyed meaning through the use of visual images, without the aid of written text. Consequently, wordless picture books have become a distinct genre within the world of literature. The wordless book is unique in that its content must be communicated solely through the use of illustrations. The reading of wordless picture book is an open-ended process in which viewers read stories by bringing their background experiences and personal histories to bear on the visual images they encount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Previous research discusses how wordless books support the development of various emergent literacy skills in children and thus are a good resource for educators in the classroom (Jalongo et al, ). Moreover, current research on teacher practices with wordless books, compared to the use of books with text, provides evidence that children infuse their own understandings of the world into wordless books, allowing for the unique creation of a story despite the lack of text (Arif & Hashim, ). Just as children are able to use their own experiences and understandings of how stories are told, caregivers are likely to employ these same strategies when telling stories from wordless books, providing opportunities for parents of all literacy levels to share books with their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research discusses how wordless books support the development of various emergent literacy skills in children and thus are a good resource for educators in the classroom (Jalongo et al, ). Moreover, current research on teacher practices with wordless books, compared to the use of books with text, provides evidence that children infuse their own understandings of the world into wordless books, allowing for the unique creation of a story despite the lack of text (Arif & Hashim, ). Just as children are able to use their own experiences and understandings of how stories are told, caregivers are likely to employ these same strategies when telling stories from wordless books, providing opportunities for parents of all literacy levels to share books with their children.…”
Section: Discussionmentioning
confidence: 99%
“…We examined narrative exchanges during the sharing of a wordless book so that mothers and children could construct unique stories and because wordless books do not require mothers to be literate. Moreover, wordless books are culturally appropriate tools that can be used to support children's emergent literacy (Jalongo, Dragich, Conrad, & Zhang, 2002) and are increasingly recognized by researchers as contexts that allow children to bring their own understanding of the world to the narrative context (Arif & Hashim, 2008).…”
Section: Reciprocal Influences On Narrative Developmentmentioning
confidence: 99%
“…The wordless picture book also guide the students to develop and express their idea in writing by looking at the picture. According to Arif and Hashim ( 2008 ), the wordless picture book is unique in that its content can be communicated solely through illustrations of the pictures. It communicates messages; the wordless picture book can be enhanced to communicate as well.…”
Section: The Reasons Were Proved In Smp Negeri 10mentioning
confidence: 99%
“…For decades, researchers have explored how wordless picture books can be used to enhance children's literacy development. They have used wordless picture books with children to elicit talk (Larrick, 1976), promote the concept of story structure (Reese, 1996), develop comprehension or the meaning-making process (Arif and Hashim, 2008;Arthur, 1982), support writing (D' Angelo, 1979) and teach visual literacy (Evans, 1992;Read and Smith, 1982;Stewig, 1988). Doake (1985) suggested that the reading of wordless picture books by mother and child can help children to develop reading-like behaviours and increase their attention span, repertoire of favourite stories and eagerness to read books repeatedly, which facilitates finding pleasure in books.…”
Section: Meaning Making From Reading Wordless Picture Booksmentioning
confidence: 99%